High-fat diet-induced aggravation of cardiovascular impairment in permethrin-treated Wistar rats - Feriani, Anouar; Bizzarri, Mariano; Tir, Meriam; Aldawood, Nouf; Alobaid, Hussah; Allagui, Mohamed Salah; Dahmash, Waleed; Tlili, Nizar; Mnafgui, Kais; Alwasel, Saleh; Harrath, Abdel Halim (Ecotoxicology and environmental safety, 2021)
This study characterized the impact of post-weaning high-fat diet (HFD) and/or permethrin (PER) treatment on heart dysfunction and fibrosis, as well as atherogenic risk, in rats by investigating interactions between HFD and PER. Our results revealed that HFD and/or PER induced remarkable cardiotoxicity by promoting cardiac injury, biomarker leakage into the plasma and altering heart rate and electrocardiogram pattern, as well as plasma ion levels. HFD and/or PER increased plasma total cholesterol, triacylglycerols, and low-density lipoprotein (LDL) cholesterol levels but significantly reduced high-density lipoprotein (HDL) cholesterol. Cardiac content of peroxidation malonaldehyde, protein carbonyls, and reactive oxygen species were remarkably elevated, while glutathione levels and superoxide dismutase, catalase and glutathione peroxidase activities were inhibited in animals receiving a HFD and/or PER. Furthermore, cardiac DNA fragmentation and upregulation of Bax and caspase-3 gene expression supported the ability of HFD and/or PER to induce apoptosis and inflammation in rat hearts. High cardiac TGF-β1 expression explained the profibrotic effects of PER either with the standard diet or HFD. Masson’s Trichrome staining clearly demonstrated that HFD and PER could cause cardiac fibrosis. Additionally, increased oxidized LDL and the presence of several lipid droplets in arterial tissues highlighted the atherogenic effects of HFD and/or PER in rats. Such PER-induced cardiac and vascular dysfunctions were aggravated by and associated with a HFD, implying that obese individuals may be more vulnerable to PER exposure. Collectively, post-weaning exposure to HFD and/or PER may promote heart failure and fibrosis, demonstrating the pleiotropic effects of exposure to environmental factors early in life. [Display omitted] •PER effect on cardiac integrity is increased when combined with an obesogenic diet.•The histopathological study showed that HFD and PER could cause cardiac fibrosis.•The cardiotoxicity is mediated by oxidative stress, inflammation and apoptosis.